2013
DOI: 10.3389/fpsyg.2013.00982
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the learning curve (once again)

Abstract: The vast majority of published work in the field of associative learning seeks to test the adequacy of various theoretical accounts of the learning process using average data. Of course, averaging hides important information, but individual departures from the average are usually designated “error” and largely ignored. However, from the perspective of an individual differences approach, this error is the data of interest; and when associative models are applied to individual learning curves the error is substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…This behavior is typically overlooked when examining aggregate behavior because different subjects have epiphanies at different points in time and so averaging over them one is left with a picture of a gradual increase in optimal behavior. This phenomenon underscores the importance of examining individual-level behavior (39)(40)(41).…”
Section: Resultsmentioning
confidence: 97%
“…This behavior is typically overlooked when examining aggregate behavior because different subjects have epiphanies at different points in time and so averaging over them one is left with a picture of a gradual increase in optimal behavior. This phenomenon underscores the importance of examining individual-level behavior (39)(40)(41).…”
Section: Resultsmentioning
confidence: 97%
“…The primary purpose of the current paper is to extend the work presented by Glautier (2013) by further applications of the MECA model and comparisons with the Rescorla-Wagner model. Two experiments are reported.…”
Section: Non-local Influences On Associative Learning: New Data and Fmentioning
confidence: 98%
“…For example, Glautier (2013) studied acquisition of predictive judgements in humans and found that in many cases the Rescorla-Wagner model provided only poor approximations to individual learning curves. Individual learning curves frequently contain large trial-to-trial changes in ratings, including regressions, which cannot be captured in standard applications of the Rescorla-Wagner model.…”
Section: Non-local Influences On Associative Learning: New Data and Fmentioning
confidence: 99%
“…Models that have been developed to account for associative learning (e.g., Rescorla and Wagner, 1972;Sutton and Barto, 1981) provide explanations and descriptions for the development of acquired associations and as such these models make concrete the parameters upon which individuals might vary. Variation conceived here might be at the level of behavior as described in the papers of this volume, but the models are also used to identify neural circuits and substrates which must be the bases for the differences described.The first three papers in this volume outline approaches to the computational analysis of individuals and provides a powerful case for how and why individual differences should be studied (Sauce and Matzel, 2013), and how the acquisition of a response or association might vary within an individual across a particular training experience (Glautier, 2013) or between individuals across the same experience (Byrom, 2013). These three contributions describe some of the elements underlying the complexity in thinking and quantitative modeling of the computational approach.…”
mentioning
confidence: 99%
“…The first three papers in this volume outline approaches to the computational analysis of individuals and provides a powerful case for how and why individual differences should be studied (Sauce and Matzel, 2013), and how the acquisition of a response or association might vary within an individual across a particular training experience (Glautier, 2013) or between individuals across the same experience (Byrom, 2013). These three contributions describe some of the elements underlying the complexity in thinking and quantitative modeling of the computational approach.…”
mentioning
confidence: 99%